Format of multicultural education for early children age in the formation of tolerance character - Ahmad Suradi; Nilawati Nilawati; Nopian Gustari (Graduate School, Universitas Negeri Yogyakarta, 2021)
This article describes the application of early childhood multicultural education to create a tolerant character in the globalization era. Multicultural education must provide contextual and tolerant moral ideals in very diverse societies such as Indonesia. The research method used is the library research method. This research is a type of descriptive-qualitative research. Data collection techniques are carried out by reviewing documents, archives, national and international repute journals, and books related to the topics discussed. The results obtained are that multicultural-based education has an important role in fostering tolerant and tolerant attitudes and working with different faiths or religions. Multicultural education to children from an early age should enable the growth of brotherhood and tolerance in togetherness from an early age to build a new generation of civilization that is more meaningful to all humankind. Multicultural education is an effort to instill the value of tolerance to children at an early age, especially to stimulate the child to be ready to accept the existence of others and have a tolerant attitude toward the pluralist.